Mitochondrial dysfunction is involved in aristolochic acid I-induced apoptosis in renal proximal tubular epithelial cells. (May 2020) - Liu, X; Wu, J; Wang, J; Feng, X; Wu, H; Huang, R; Fan, J; Yu, X; Yang, X
Aristolochic acid (AA) is a compound extracted from the Aristolochia species of herbs. AA exposure is associated with kidney injury known as aristolochic acid nephropathy (AAN). Proximal tubular epithelial cell (PTEC) is the primary target of AA and rich in mitochondria. Recently, increasing evidence suggests that mitochondrial dysfunction plays a critical role in the pathogenesis of kidney disease. However, the status of mitochondrial function in PTEC after exposure to AA remains largely unknown. The aim of this study was to explore the effect of aristolochic acid I (AAI) on cell apoptosis and mitochondrial function in PTEC. Normal rat kidney-52E (NRK-52E) cells were exposed to different concentrations of AAI for different time periods. Cell viability was detected by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide, cell apoptosis was analyzed by flow cytometry, and the expression of cleaved caspase-3 by Western blotting. Mitochondrial function was evaluated by reactive oxygen species (ROS), mitochondrial membrane potential (MMP), mitochondrial DNA (mtDNA) copy number, and adenosine triphosphate (ATP). It was found that AAI reduced cell viability and increased cell apoptosis in a dose- and time-dependent manner. In parallel to increased apoptosis, NRK-52E cell manifested signs of mitochondrial dysfunction in response to AAI treatment. The data indicated that AAI could increase ROS level, lower MMP, decrease mtDNA copy number, and reduce ATP production. In addition, Szeto-Schiller 31, a mitochondria-targeted antioxidant peptide, attenuated AAI-induced mitochondrial dysfunction and apoptosis. Our study depicted significant aberrant of mitochondrial function in AAI-treated NRK-52E cell, which suggested that mitochondrial dysfunction may be involved in AAI-induced apoptosis in PTEC.